2015
DOI: 10.2188/jea.je20140198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Children’s Mental Health Problems and the Effectiveness of Population-Level Family Interventions

Abstract: The prevalence of mental health problems among children and adolescents is of growing importance. Intervening in children’s mental health early in life has been shown to be more effective than trying to resolve these problems when children are older. With respect to prevention activities in community settings, the prevalence of problems should be estimated, and the required level of services should be delivered. The prevalence of children’s mental health disorders has been reported for many countries. Preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 49 publications
(48 reference statements)
3
39
0
2
Order By: Relevance
“…Knowledge is limited in terms of incidence and its relation to gender, social and demographic factors . Hence, a systematic identification of children's developmental and behavioural problems is required , which has also been called for by Swedish national authorities. A prevalence study carried out in the USA revealed that more than one‐fifth of the child population three years or younger had mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge is limited in terms of incidence and its relation to gender, social and demographic factors . Hence, a systematic identification of children's developmental and behavioural problems is required , which has also been called for by Swedish national authorities. A prevalence study carried out in the USA revealed that more than one‐fifth of the child population three years or younger had mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords : Parenting support ; parenting program ; children ; parental needs ; prevention ; access to service; emotional and behavioral disorders REVISION SOUMISE LE 22.06.2018 Les études épidémiologiques sur la santé mentale des enfants révèlent que près d'un enfant sur cinq présente des difficultés émotionnelles ou comportementales sévères, ces chiffres variant de 10 à 20% selon les pays et les méthodes utilisées [1][2][3]. Ces difficultés peuvent fortement toucher la vie quotidienne de l'enfant et entraver les relations avec les pairs, le fonctionnement familial et scolaire.…”
Section: Resultsunclassified
“…De plus, si ces difficultés restent non traitées, la moitié de ces enfants risque d'éprouver des séquelles à long terme, que ce soit à l'adolescence ou à l'âge adulte [4]. Malgré ce constat alarmant, seule une minorité d'enfant (environ 25%) a accès à des services professionnels, du moins en Amérique du Nord [1,5]. En France, il n'existe pas à notre connaissance de données similaires pour les enfants, mais l'accès aux services de santé mentale semble aussi restreint à une minorité d'individus [6].…”
Section: Resultsunclassified
“…Similar proportions of children also appear to experience internalizing and externalizing disorders (Kato et al, 2015).…”
Section: Prevalence Of Child Mental Healthmentioning
confidence: 97%
“…It has been suggested that child behaviour and emotional problems have become increasingly common and may lead to, or are associated with, their poor mental health, with some 10.0% to 20.0% of children found to have 'clinically meaningful total difficulty' as assessed by the Child Behaviour Check List (CBCL) (Kato et al, 2015). Similar proportions of children also appear to experience internalizing and externalizing disorders (Kato et al, 2015).…”
Section: Prevalence Of Child Mental Healthmentioning
confidence: 99%